2023
DOI: 10.3390/w15071276
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Natural Coagulants for Plastic Recycling Industry Wastewater Treatability

Abstract: The plastic recycling industry generates a high volume of wastewaters. In this study, an unprecedented use of Moringa oleifera and tannin (Acacia mearnsii bark) associated with magnetite was proposed for the treatment of these wastewaters. The response surface method (RSM) and central composite rotational design (CCRD) methodology was applied to optimize the influence of operational variables (pH, temperature, electrical conductivity, turbidity, apparent color, chemical oxygen demand (COD), and total solids) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…described the botany of Moringa oleifera, which is a small, graceful, deciduous tree with sparse foliage, often resembling a leguminous species at a distance, especially when in ower, but immediately recognized when in fruit. [23]investigated the use of Moringa oleifera seed powder in the treatment of industrial wastewater. The study found that Moringa oleifera seed powder effectively removed up to 92% of pollutants from the wastewater.…”
Section: Review Of Literaturementioning
confidence: 99%
“…described the botany of Moringa oleifera, which is a small, graceful, deciduous tree with sparse foliage, often resembling a leguminous species at a distance, especially when in ower, but immediately recognized when in fruit. [23]investigated the use of Moringa oleifera seed powder in the treatment of industrial wastewater. The study found that Moringa oleifera seed powder effectively removed up to 92% of pollutants from the wastewater.…”
Section: Review Of Literaturementioning
confidence: 99%